Resonantly pumped, Q-switched Ho:YLF laser with output energy of 5 mJ at 1 kHz - Kwiatkowski, Jacek; Swiderski, Jacek; Zendzian, Waldemar; Jabczynski, Jan Karol; Gorajek, Lukasz; Kaskow, Mateusz (Photonics Letters of Poland, 2014)
A continuous-wave (CW) and Q-switched operation of a Ho:YLF laser resonantly, single-pass pumped by a Tm: fiber laser operating at a wavelength of 1940nm is presented. At room temperature, for an output coupler of 40% transmission, a maximum CW output power of 11.5W for 32.5W of incident pump power was achieved, corresponding to a slope efficiency of 40%. Applying Q-switching operation, and under CW pumping regime, the pulse repetition frequency (PRF) was changed from 1 to 10kHz. The maximum average output power of 11.23W at the PRF of 10kHz was obtained. Lowering the PRF to 1kHz allows achieving pulse energy of 4.97mJ in a 19ns pulse corresponding to the maximum peak power of 260kW. The Ho:YLF laser operated at the wavelength of 2050.5nm with a FWHM line width of 1.09nm. The output parameters of the laser radiation are sufficient enough to be used for range finding or for pumping mid-infrared optical parametric oscillators. Full Text: PDF References K. Scholle, S. Lamrini, P. Koopmann, P. Fuhrberg, chapter 21 in Frontiers in Guided Wave Optics and Optoelectronics, INTECH, ISBN 978-953-7619-82-4, 2010. J. Kwiatkowski, J.K. Jabczynski, W. Zendzian, L. Gorajek, M. Kaskow, "High repetition rate, Q-switched Ho:YAG laser resonantly pumped by a 20 W linearly polarized Tm: fiber laser", Appl. Phys. B 114, 395 (2014). CrossRef W. Koen, C. Bollig, H. Strauss, M. Schellhorn, C. Jacobs, M.J.D. Esser, "Compact fibre-laser-pumped Ho:YLF oscillator?amplifier system", Appl. Phys. B 99, 101 (2010). CrossRef Y.J. Zhang, G. Li, Y.Y. Zhao, Y.N. Chen, "In-band pumped Ho:YAP laser by Tm-Doped fiber laser at 1936 and 1948 nm, respectively", Laser Phys. 22, 415 (2012). CrossRef H. Chen, D.Y. Shen, X.D. Xu, T. Zhao, X.F. Yang, D.H. Zhou, J. Xu, "High-power 2.1 ?m Ho:Lu1.5Y1.5Al5O12 laser in-band pumped by a Tm fiber laser ", Laser Phys. Lett. 9, 26 (2012). CrossRef J.W. Kim, J.I. Mackenzie, D. Parisi, S. Veronesi, M. Tonelli, W.A. Clarkson, "Efficient in-band pumped Ho:LuLiF4 2?m laser", Opt. Lett. 35, 420 (2010). CrossRef B.Q. Yao, X.M. Duan, Y.L. Ju, Y.Z. Wang, "Continuous wave operation of singly-doped Ho:LSO laser at room temperature", Laser Phys. 21, 1888 (2011). CrossRef X.J. Cheng, J.Q. Xu, M.J. Wang, B.X. Jiang, W.X. Zhang, Y.B. Pan, "Ho:YAG ceramic laser pumped by Tm:YLF lasers at room temperature", Laser Phys. Lett. 7, 351 (2010). CrossRef A.S. Kurkov, V.A. Kamynin, E.M. Sholokhov, A.V. Marakulin, "Mid-IR supercontinuum generation in Ho-doped fiber amplifier", Laser Phys. Lett. 8, 754 (2011). CrossRef B.M. Walsh, G.W. Grew, N.P. Barnes, "Energy levels and intensity parameters of Ho3+ ions in GdLiF4, YLiF4 and LuLiF4", J. Phys.: Condens. Matter 17, 7643 (2005). CrossRef